2019
DOI: 10.1186/s13756-019-0463-0
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection in Xi’an, China: epidemic characterization, risk factors to false positives and potential utility of the sample-to-cutoff index to identify true positives using Architect HIV Ag/Ab combo

Abstract: BackgroundIn China, although tremendous efforts has been made, the HIV/AIDS is still not controlled.ObjectivesThe study was carried out to determine the epidemic of HIV infection in Xi’an, analyse false positives (FP) risk factors and potential utility of sample-to-cutoff index to identify true positives using Architect HIV Ag/Ab Combo.MethodsA retrospective review for HIV screening by Architect HIV Ag/Ab Combo was performed in a teaching hospital in Xi’an between 2015 and 2016. The prevalence of HIV, positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Results also showed that most patients with false-positive results were elders and females, which was consistent with previous studies. 17,18 Recent studies revealed that many factors, such as cancers, rheumatoid factors, autoimmune diseases, and pregnancy, might lead to poor specificity in HIV screening by the 4th-generation assay and cause an indeterminate result for the WB test. [19][20][21][22][23][24] More elderly patients in the false-positive group are more likely to suffer from underlying diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Results also showed that most patients with false-positive results were elders and females, which was consistent with previous studies. 17,18 Recent studies revealed that many factors, such as cancers, rheumatoid factors, autoimmune diseases, and pregnancy, might lead to poor specificity in HIV screening by the 4th-generation assay and cause an indeterminate result for the WB test. [19][20][21][22][23][24] More elderly patients in the false-positive group are more likely to suffer from underlying diseases.…”
Section: Discussionmentioning
confidence: 99%
“…By the end of September 2018, there were 849,602 people living with HIV (PLWH) in mainland China [ 15 ]. The epidemic is severe in some midwest provinces (Sichuan, Chongqing, Guizhou, Hunan, Henan) and border communities (Xinjiang, Guangxi, Guandong), with annual new HIV/AIDS cases more than 5000 [ 16 - 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using a combination of independent sample testing and different platform testing, for confirmation, we found that 85% of LP&E results were FP and therefore, LP&E result prevalence can be used as an indicator of FP rate. In other settings, the PPV for this assay approached 100% when using a higher positive threshold than recommended by the manufacturer (S/CO over 30) in European and Asian populations [ 7 9 ]. Given the high proportion of FP results among LP&E (S/CO <30) in our setting, the use of a higher threshold for positivity helped to identify cases likely to be false positive in our context, whereas the high proportion that tested negative when testing an independent sample highlights the importance of confirming HIV serology on a separately collected sample.…”
Section: Discussionmentioning
confidence: 99%
“…FP results usually generate LP&E S/CO signals as seen by other centres [ 2 , 6 , 7 ]. Using a combination of independent sample testing and different platform testing, for confirmation, we found that 85% of LP&E results were FP and therefore, LP&E result prevalence can be used as an indicator of FP rate.…”
Section: Discussionmentioning
confidence: 99%